Youth Response to Rape: Rape Myths and Social Support. Issue 11 (June 2021) - Lichty, Lauren F.; Gowen, L. Kris
Adolescents and young adults face the highest incidence of sexual assault, yet only limited research focuses on the experience of adolescent survivors, adolescent rape myth acceptance, or the ways youth respond to rape. Survivors tend to disclose to at least one person, typically peers, and the response, whether positive or negative, can impact well-being and help-seeking behaviors. Focus groups across Oregon, a leader in state-level comprehensive sexuality education policy, solicited high school-student reactions to an alcohol-involved rape scenario. These rich-case participants had taken comprehensive sexuality education classes and were affiliated with health and sexuality organizations. These youth were anticipated to showcase best possible outcomes resulting from current sexuality education practices. After hearing a hypothetical scenario involving a friend's experience with alcohol-involved sexual assault, participants were asked how they would respond. Participants spontaneously discussed whether the actions described constituted rape, often relying on victim-blaming rape myths as evidence. Alcohol use was a critical factor in interpretations. Female use increased her perceived culpability and male use decreased his. After assessing blame and whether the incident constituted rape, youth described three types of support (informational, instrumental or practical, and emotional support) they would offer as well as barriers when responding to the victim and intentions to hold victims accountable. These responses paint a concerning portrait of the ways youth make sense of sexual violence and consider responding to a friend's disclosure. Sexuality education policy mandates and intervention programs must target the problematic links between alcohol, rape, and rape myths while reinforcing non-victim-blaming support.